A H2S and I− dual-responsive supramolecular polymer constructed via pillar[5]arene-based host–guest interactions and metal coordination. Issue 8 (13th February 2018) - Wang, Pi; Ma, Jiao; Xia, Danyu
Abstract : A supramolecular polymer was designed and prepared by self-assembly of a pillar[5]arene dimer (AA-type), constructed from Ag-coordination, and a homoditopic (BB-type) guest (G ). The supramolecular polymer displayed H2 S and I − dual responsiveness due to the sensitivity of Ag + to H2 S and I − . Abstract : Stimuli responsive supramolecular polymers have received great attention during the last few decades because of their wide applications in the areas of nano- and bio-technology. Among various stimuli, gas and ions play important roles both in the environment and in life science. However, hydrogen sulfide (H2 S)and iodide ion (I − ) stimuli responsive supramolecular polymers are not commonly reported. Furthermore, supramolecular polymers which can be responsive to both H2 S and I − are even more rarely reported. Herein, we synthesized a mono-functionalized pillar[5]arene host molecule with a pyridine group which can coordinate to a silver ion to fabricate a pillararene dimer, providing a facile way to obtain a pillararene-based dimer. Thus a H2 S and I − dual-responsive supramolecular polymer was constructed by self-assembly of the pillararene dimer and a homoditopic guest in chloroform.